No short-term effects of calorie-controlled Mediterranean or fast food dietary interventions on established biomarkers of vascular or metabolic risk in healthy individuals - Parčina, Marijo; Brune, Maik; Kaese, Vareska; Zorn, Markus; Spiegel, Rainer; Vojvoda, Valerija; Fleming, Thomas; Rudofsky, Gottfried; Nawroth, Peter Paul (Nutrition research and practice, 2015)
Parcina M, et al. Nutr Res Pract. 2015 Apr;9(2):165-173. https://doi.org/10.4162/nrp.2015.9.2.165
Gesehen am 30.06.2020